BUHARÎ İLE EBÛ DAVUD'UN HOCASI MÜSEDDED B. MÜSERHED VE HADİS İLMİNDEKİ YERİ - Dinçoğlu, Mehmet (My University, 2014)
Ünlü Muhaddis el-BuhArî (256/869), fakih muhaddislerden Ebû DAvud esSicistanî (275/889) ile birçok hadis Alimine hocalık yapmış ve onlara önemli ölçüde kaynaklık etmiş hadisçilerden biri de Müsedded b. Müserhed'tir (228/843). Onun Basra'lı muhaddisler arasında ilk Müsned adlı eseri yazdığı bilinmektedir. Hadis tarihinde rastlanılan ilk şerhlerden biri, Ebû Hasen Muhammed b. Eslem Tusi'nin (ö.h.242-Tus) "Şerhu Müsned i'l-Müsedded" isimli Müsedded'in Müsned i üzerine yapılan şerhidir. Ancak ne bu şerh ne de Müsedded'e ait bir eserin günümüze ulaştığına dair herhangi bir bilgi yoktur. Ayrıca Müsedded'in hayatı ve hadis ilmindeki yeri ile ilgili müstakil bir çalışmamın da bulunmayışı, Müsedded ile ilgili çalışmamızı sağlamıştır. Bu makalede konu olarak, musannif olan Müsedded b. Müserhed'in hayatı ve onun hadis ilmindeki yeri ele alınmıştır.

Musedded b. Muserhed (228/843) was one of the hadith scholars who taught renowned Muhaddis el-Buhiri (256/869) and Ebi Divud es-Sicistani (275/889) and was quoted significantly by many other hadith scholars. It is known that he was the first scholar among muhaddises from Basra who wrote the treatise named Musnad. One of the first annotations encountered in the history of hadith is Ebi Hasen Muhammed b. Eslem Tusi's (ö.h.242-Tus) annotation named which is made on the Müsedded's Musnad. However, there is no any evidence about neither this -Şerhu Müsned - nor a work on Müsedded has reached out up to present date. Furthermore, lacking of any individual study related to the Müsedded's life and its * Yrd. Doç. Dr., Muş Alparslan üniversitesi İslami İlimler Fak. Hadis Anabilim Dalı öğretim üyesiplace in the science of Hadith has enabled us to work on this article.In this study, Müsedded b. Müserhed's life and his place in the science of hadith are handled as the subject.
Buharî and Ebû Davûd's Master Müsedded b. Müserhed and his Place in The Science of Hadith
Keywords: Din Bilimi